Bauran Promosi Coffee Shop Wiedu di Instagram - Putri Ayu Febriyanti; Anne Ratnasari (Bandung Conference Series: Communication Management, 2022)
Abstract. one of the important factor to achieve success for a business is promotion. The coffee shop has now expanded to become one of the places frequented by young people to fulfill their lifestyle. Coffee shops are growing rapidly along with the lifestyles of young people who like to hang out at coffee shops. Wiedu Coffee Shop takes advantage of this business opportunity in its business. The marketing target is mainly aimed at young people, so the right promotion media is through Instagram social media which is often visited by young people on their smartphones. The author does a promotion mix or marketing communication mix with promotional tools to communicate product value and build relationships with customers. The promotional tools applied are advertising, sales promotion, events and experiences, public relations and publicity, online and social media marketing, mobile marketing, direct and database marketing, and personal selling. The purpose of this study was to identify the promotional mix at the Wiedu Coffee Shop. This research applies qualitative research methods with descriptive study research. Data obtained through direct observation, interviews, and documentation. The results obtained are the theory of the promotion mix at the Wiedu Coffee Shop. This shows that Wiedu Coffee Shop is in the mix of advertising, sales promotion, public relations, personal selling, and direct marketing. The result of this research is that Wiedu Coffee Shop has implemented promotion mix through Instagram social media. Abstrak. Promosi merupakan salah satu faktor penting untuk meraih kesuksesan bagi suatu usaha. Coffee shop kini telah merambah menjadi salah satu tujuan yang kerap dikunjungi anak muda guna untuk memenuhi gaya hidup mereka. Coffee shop semakin berkembang pesat seiring dengan lifestyle anak muda yang gemar nongkrong di coffee shop. Wiedu Coffee Shop memanfaatkan peluang usaha tersebut dalam bisnisnya. Target pemasaran terutama ditujukan pada anak muda, sehingga media promosi yang tepat yaitu melalui media sosial Instagram yang kerap dikunjungi anak-anak muda dalam smartphone mereka. Penulis melakukan bauran promosi yang mana bauran komunikasi dilakukan dengan peralatan promosi untuk mengomunikasikan nilai produk dan menciptakan relasi dengan customer. Adapun alat promosi yang diterapkan yaitu personal selling, online and social media marketing, advertising, sales promotion, public relations and publicity, direct and database marketing, mobile marketing, serta events and experiences. Tujuan penelitian ini untuk mengidentifikasikan bauran promosi pada Wiedu Coffee Shop. Penelitian ini menggunakaan metode kualitatif dengan pendekatan deskriptif. Penelitian studi secara deskriptif. Data yang diperoleh melalui kegiatan pengamata, sesi wawancara, serta sesi dokumentasi. Berdasarkan penelitian ini maka diperoleh hasil penelitian yaitu teori bauran promosi di Wiedu Coffee Shop sudah dilaksanakan. Hal tersebut menunjukkan bahwa Wiedu Coffee Shop berada di bauran iklan atau promosi, relasi dengan masyarakat, penjual individu, serta sarana marketing. Oleh sebab itu dapat dikatakan bahwa Wiedu Coffee Shop telah menerapkan bauran promosi melalui media sosial Instagram.